2015
DOI: 10.1051/radiopro/2015011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of statistical changes on internal dosimetry

Abstract: -Currently, internal dosimetry evaluations are performed using reference computational phantoms. There are significant discrepancies in the organ absorbed doses regarding the variations in organ mass. In this study, to investigate the effects of changes in the lung mass on the results of internal dosimetry, 98 similar mathematical phantoms were developed, so that the masses of their lungs changed with a Gaussian distribution. The lung was selected as the source. Doses delivered to the organs/tissues for photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Considering that a specific organ mass differs from one person to another, one of the reasons for the deviation associated with phantoms is the variations in the organ mass. The coefficient of variation of the dose related to the lung mass has been calculated to be 18%, which can fully explain the aforementioned 13% discrepancy (Sajjadi et al, 2015 GEANT4 and DOSE3D) revealed that the variations among the results were relatively small. In the worst situation, the transport calculation method may result in up to 10% differences in organ absorbed doses (ICRP, 2010).…”
Section: The Dose Of the Lung And Other Organs For The Ornl Referencementioning
confidence: 75%
See 1 more Smart Citation
“…Considering that a specific organ mass differs from one person to another, one of the reasons for the deviation associated with phantoms is the variations in the organ mass. The coefficient of variation of the dose related to the lung mass has been calculated to be 18%, which can fully explain the aforementioned 13% discrepancy (Sajjadi et al, 2015 GEANT4 and DOSE3D) revealed that the variations among the results were relatively small. In the worst situation, the transport calculation method may result in up to 10% differences in organ absorbed doses (ICRP, 2010).…”
Section: The Dose Of the Lung And Other Organs For The Ornl Referencementioning
confidence: 75%
“…The dose (and S value) for photons is inversely proportional to the mass with the power, ranging from 1/2 to 1 at energies between 10 and 4000 keV (i.e., 1/2 for 4000 keV and 1 for 10 keV) (Eq. (2)) (Sajjadi et al, 2015) proportional to the mass −2/3 (Eq. (3)) (Snyder, 1970;Stabin et al 2005;Hansson, 2012):…”
Section: Investigating Changes In the Lung Absorbed Dose With Changesmentioning
confidence: 99%